Pemanfaatan Rosella dan Jahe dalam Pembuatan Produk Minuman Herbal (Roseja) untuk Meningkatkan Daya Imun di SMK Karya Bhakti Pada Massa Pandemi Covid-19 - Kusnadi Kusnadi; Rosaria Ika Pratiwi; Ahmad Aniq Barlian (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The selection of herbal drink products needs to consider the high antioxidant content to increase immune power during the Covid-19 pandemic. The purpose of the proposed community service activity (PKM) is to foster student entrepreneurial interest through making herbal drinks made from rosella and ginger (Roseja) to create understanding, and knowledge and will provide opportunities for the development of creative potential and innovation. The priority issues that will be handled in this PKM activity are 1) Socialization to students of SMK Karya Bhakti, Brebes Regency, Central Java about the use of rosella and ginger as the basis for making Roseja herbal drink products (rosella and ginger) that are safe for consumption, 2) improving students' skills SMK to make products with a concentration of additives, 3) increase the motivation of SMK students to carry out promotional activities to market products to consumers. The target audience in this PKM activity is participants in community service activities. The participants of this activity were students of class XII of SMK Karya Bhakti, Brebes Regency. The approach method used to overcome the problems faced by partners is the method of training and socializing the manufacture of Roseja herbal drink products that are safe for consumption. The results obtained from this activity are increasing understanding of the use and manufacturing methods as well as motivation to market herbal drink products from the combination of rosella and ginger. The percentage shows that 100% can understand the material and can practice how to make herbal drinks. As many as 80% were motivated to implement and develop rosella ginger herbal drink products, and 70% of the participants were motivated to market them.